O uso da Ead na capacitação continuada de servidores numa Instituição Federal de ensino - Bernardo, Ericson Robson de Sousa (2015)
The world is going through profound and rapid change in which public organizations have been impacted, particularly with the inclusion and increasing advancement of technology digital and resizing markets faced with the need to deliver better results to the society in which their survival depends on their ability to learn to learn (ASSMAN, 1998; CHOO, 2006; Morgan, 2002), and in people your starting point for resolving current challenges problems and coping adding greater competitiveness and organizational efficiency (FLEURY, 2002). The theoretical models contextualizes Management in Public Administration (SANABIO; SANTOS; DAVID, 2013) and the emergence of the paradigm of Public Organizations Learners (ASSMAN, 1998), addresses the organizational learning and management skills. It presents the inclusion of distance education in public organizations (ENAP, 2006), its historical evolution, its use for training purposes and ends dealing with resistances and challenges of distance learning for learning in public organizations. The aim of this research is to investigate the use of Distance Education (EAD) in the training of technical and administrative staff of the Rectory of the Federal Institute of Education, Science and Technology of Paraíba (IFPB). Therefore, the following specific objectives were outlined: (a) describe the current situation of the use of EAD for Technical and Administrative server training purposes within the Rectory of IFPB, (b) identify the EAD as a training tool in service skills development, and (c) to identify strengths and weaknesses in the use of distance learning for training purposes. The methodology used in the study is to be classified as to their purpose as applied, how to approach the problem in both qualitative and quantitative, as the achievement of the in exploratory purposes and with respect to the method, a case study in which the IFPB It will be the organization studied. For data collection were used instruments: document analysis, questionnaire and structured interview. The questionnaire was applied to the Technical and Administrative servers of the Rectory of IFPB through the electronic forms tool Google Docs. A structured interview was applied to the management of Professional Training and Qualification properly recorded, transcribed literally and converted into protocol for thematic categorization extraction. The treatment and analysis of the results was performed by the triangulation approach, seeking to identify converging lines in understanding the proposed problem. The survey results indicate that the use of distance learning in the training of Technical and Administrative servers could be a strategic tool for organizational learning promoting the development of collective skills for the promotion of individual skills and optimizing the use of resources for this purpose, especially in the face of severe financial constraints. Also points out the advantages and challenges in its execution, in compliance with the existing legal regulations. The study concludes that the use of distance learning in the training of Technical and Administrative servers can add greater organizational efficiency to its internal processes through continuous learning and the achievement of its institutional mission.